Development of solar dryer system for food drying purposes - Nabilah, Harmain (2012)
The objective of this work is to design, develop and evaluate performance of an indirect solar dryer prototype in a passive and active mode using thermal energy storage and without thermal energy storage for the drying of kiwifruits. Drying is one of the oldest methods using solar energy where the product such as vegetables, fruits, fish, and meat to be dried exposed directly to the sun. This method has many disadvantages such as spoilt products due to rain, wind, dust, insect infestation, animal attack and fungi. Foods should be dried rapidly, but the speed of drying will cause the outside becomes hard before the moisture inside has a chance to evaporate and it will affect the quality of dried product due to over drying. The design of a functional solar dryer system would minimize these disadvantages. This design of both modes was employed and has compared with the performance testing through parameters such as temperature, air velocity, collector efficiency and weight loss. It was shown that the use of this type of solar dryer reduced the drying time significantly and essentially provide better product quality compared with conventional drying method. The effect of temperature to moisture contents against time and rate of drying are studied in this research.